Essepiù : bollettino dei gruppi auto-aiuto delle persone sieropositive dell'ASA di Milano. (Milano : ASA, 1991)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijksRedactie : Via Torricelli 19, 20136 Milano
Italiaans
Periodiek